Antibiofilm and Enzyme Inhibitory Potentials of Two Annonaceous Food Spices, African Pepper (Xylopia aethiopica) and African Nutmeg (Monodora myristica) - Alfred Ngenge Tamfu; Ozgur Ceylan; Selcuk Kucukaydin; Mehmet Ozturk; Mehmet Emin Duru; Rodica Mihaela Dinica (Foods, 2020)
Food pathogens represent an important health threat, and it is relevant to study the effect of foodstuffs such as spices which can inhibit bacterial growth. This study reports the antimicrobial, antibiofilm, and enzyme (Acetylcholinesterase, Butyrylcholinesterase, urease, tyrosinase) inhibitory activities of two medicinal food spices belonging to the Annonaceae family, Monodora myristica and Xylopia aethiopica. GC-MS (gas chromatography mass spectrometry) analysis of silylated samples of Methanol-Dicloromethane (50:50) extracts of both plants led to the identification of nine compounds in M. myristica and seven compounds in X. aethiopica. M. myristica and X. aethiopica had the same minimum inhibitory concentration (MIC) values of 0.625 mg/mL and 2.5 mg/mL on C. albicans and E. coli, respectively. However, M. myristica had better activity than X. aethiopica on Staphylococcus aureus, while Pseudomonas aeruginosa was more susceptible to X. aethiopica than M. myristica. The lowest MIC value was 0.1325 mg/mL, exhibited by M. myristica on S. aureus. Both extracts showed good antibiofilm activity. On S. aureus, at the same concentration, M. myristica had better antibiofilm activity than X. aethiopica. On E. coli and Candida albicans, X. aethiopica had better antibiofilm activity than M. myristica at the same concentration. X. aethiopica showed better violacein inhibition in Chromobacterium violaceum CV12472, as its percentage inhibition of violacein varied from 80.5% ± 3.0% at MIC to 5.6 ± 0.2 at MIC/8, as compared to M. myristica with 75.1% ± 2.5% at MIC and 15.5% ± 1.1% at MIC/8. The anti-motility activity by swimming and swarming inhibition on P. aeruginosa PA01 was low at test concentrations and in both models, M. myristica showed higher motility inhibition than X. aethiopica. Although in enzyme inhibitory assays all extracts had low inhibitions compared to standards tested at the same concentrations, the results show that these plants can be used to manage food-borne infections.